Migration and the welfare state: Dynamic political-economy theory - Assaf Razîn; Efraim Sadka; Benjarong Suwankiri (Center for Economic Studies and ifo Institute (CESifo), 2010)
We model an overlapping-generations economy with two skill levels: skilled and unskilled. The welfare-state is modeled simply by a proportional tax on labor income to finance a demogrant in a balanced-budget manner. Therefore, some (the unskilled workers and old retirees) are net beneficiaries from the welfare state and others (the skilled workers) are net contributors to it. Migration policies are set to determine the total migration volume and its skill composition.We characterize subgame-perfect Markov political-economic equilibria consisting of the tax rate (which determines the demogrant), skill composition and the total number of migrants. We distinguish between two voting behaviors: sincere and strategic voting.
Keywords: H00; F20; F13; 330; Migrationspolitik; Einwanderungsrecht; Qualifikation; Sozialversicherungsfinanzierung; Umlageverfahren; Einwanderung; Wahlverhalten; Sozialstaat; Public Choice; Theorie